Prognostic value of gut microbiota and low-density lipoprotein cholesterol subfractions in patients with ST-segment elevation myocardial infarction - Xia, Siliang; Liu, Yun; Wang, Mengzhu; Liu, Dandan; Zhang, Xiaobing; Lin, Ling; Wen, Ming; Ji, Shushen; Li, Jiaying; Zhang, Xiangming; Jiang, Huihui (Frontiers in Immunology, 2025)
ObjectiveGut dysbiosis and the distribution of low-density lipoprotein cholesterol (LDL-C) subfractions have been implicated in cardiovascular risk among patients with ST-segment elevation myocardial infarction (STEMI). However, the prognostic significance of LDL-C subfractions in relation to gut microbiota composition remains largely unexplored. This study aimed to assess differences in gut microbiota profiles and LDL-C subfraction distribution between patients with STEMI with and without major adverse cardiovascular events (MACEs) and to elucidate their potential interplay.MethodsWe enrolled 32 male population without coronary heart disease and 66 male patients with STEMI. Fecal samples were analyzed via 16S rDNA gene sequencing to assess gut microbiota diversity and composition. Plasma LDL-C subfractions were quantified using the Quantimetrix Lipoprint LDL System.ResultsAmong these 66 STEMI patients, 18 experienced MACEs during a median follow-up of 13 months (MACEs group), while 18 age-matched event-free patients were selected as controls (Non-MACEs group). Significant differences in gut microbiota composition, but not diversity, were observed between the two groups, with the Non-MACEs group exhibiting a greater number of marker genera. Although no significant differences were found in LDL-C subfractions between groups, multiple significant negative correlations were identified between gut microbiota and LDL-C subfractions in the MACEs group, including between Coprococcus and LDLC-4 (ρ=-0.5488, P<0.05), between Coprococcus and LDLC-5 (ρ=-0.6418, P<0.01), between Coprococcus and LDLC-6 (ρ=-0.4988, P<0.05), between UCG-002 and LDLC-4 (ρ=-0.4948, P<0.05), and between Christensenellaceae_R-7_group and LDLC-4 (ρ=-0.5032, P<0.05). Furthermore, gut microbiota markers demonstrated superior predictive performance for MACEs compared to LDL-C subfractions, with UCG-002, Christensenellaceae_R-7_group, and NK4A214_group achieving AUC values >0.75.ConclusionGut microbiota, particularly UCG-002, Christensenellaceae_R-7_group, and NK4A214_group, exhibit greater prognostic potential for MACEs than LDL-C subfractions. These findings highlight the role of gut microbiota in post-STEMI risk stratification, underscoring its potential as a target for future cardiovascular interventions.